COMMUNITY AGGREGATION IN VIRTUAL WORLDS. CASE STUDY ‟2 STARWAKE” - COSTINA, Andrei (Studia Universitatis Babeș-Bolyai Ephemerides, 2015)
The paper aims to study social aggregation in virtual spaces determined by digital communities where action is no longer action per se, but transforms into concept and thought, and the environment is created solely from the interaction between the individuals. Besides studying the communities in the informational society there is the need to delve for a better understanding of the virtual society phenomenon from the perspective of the individual as a part of the system. In this respect, there is a lot to explore on the offline social aspects of the online addicted.